Pengaruh Persepsi Dukungan Organisasi Dan Pemberdayaan Psikologis Terhadap Kinerja Yang Dimediasi Organizational Citizenhip Behavior.Di Badan Pusat Statistik Provinsi Daerah Istimewa Yogyakarta - Harin Ihtian (Universitas Muhammadiyah Yogyakarta, 2014)
The objective of this research is to find out these following matters: the influence perceived organizational support toward job performance, the influence psychological empowerment toward job performance, the influence perceived organizational support toward OCB, the influence psychological empowerment toward OCB, also the influence perceived organizational support and psychologival empowerment on Job performance mediated organizational citizenship behavior in Badan Pusat Statistik Provinsi Daerah Istimewa Yogyakarta, data collected from 77 employe.This research uses survey and questioners as the tools in collecting data. The data were obtained from 77 employee. Data analyzed using multi regression with SPSS 17 program and path analyzed. The result of the research showed the following result: perceived organizational support haven’t positive significant effect on job performance, psychological empowerment has positive significant on job performance, perceived organizational support has positive significant effect on OCB, psychological empowerment has positive significant on OCB, also OCB has positive significant effect mediator for perceived organizational support and psychological empowerment toward jop performance.